Mid-lecture commit

This commit is contained in:
Blizzard Finnegan 2022-03-03 13:10:36 -05:00
parent d403fc1eb1
commit d4fef57913
No known key found for this signature in database
GPG key ID: 8D7B42E0247CBE40

View file

@ -0,0 +1,82 @@
% File: 20-01-2022.tex
% Created: 12:28:35 Thu, 20 Jan 2022 EST
% Last Change: 12:28:35 Thu, 20 Jan 2022 EST
%
\documentclass[letterpaper]{article}
\usepackage{amsmath}
\usepackage{graphicx}
\usepackage{cancel}
\usepackage{amssymb}
\usepackage{listings}
\usepackage[shortlabels]{enumitem}
\usepackage{soul}
%\usepackage[smartEllipses,hashEnumerators,hybrid]{markdown}
\usepackage{geometry}
\usepackage{dirtytalk}
\usepackage{mathtools}
\usepackage{lplfitch}
\geometry{portrait, margin=1in}
%\begin{minted}[linenos,bgcolor=LightGray]{[language]}
\date{02/17/2022}
\title{%
Induction and Recursion\\
\large MATH--190--01 : Discrete Mathematics for Computing}
\author{Blizzard MacDougall}
\begin{document}
\maketitle
\pagenumbering{arabic}
We've seen that $\sum\limits^{100}_{i=0}k=\frac{100*101}{2}=5050$
Now we're going to find out \emph{why}.
To do this, we'll use induction.
This is a demonstration of how induction generally works.
All of these steps need to explicitly be shown.
First, we need to prove that our predicate is true for one case.
In this case, we need need to show that $\sum\limits^{1}_{k=1}k=1=\frac{1(1+1)}{2}=1$
Next, we must show that for every $n\geq a$, if $P(n)$ is true, $P(n+1)$ is also true.
To do this, suppose that the aforementioned case is in fact true. Then show that
$P(n+1)$ is true. In our case, we assume that $\sum\limits^{n}_{k=1}k=\frac{n(n+1)}{2}$
is in fact true. Now, we need to prove that it works when $n=n+1$.
So, we can say the following:
\begin{equation}
\begin{split}
\sum^{n+1}_{k=1} k=\sum^{n}_{k=1}k + (n+1)\\
=\frac{n(n+1)}{2} +(n+1)\\
=\frac{n(n+1)}{2}+\frac{2(n+1)}{2}\\
=\frac{n^2+n+2n+2}{2}\\
=\frac{n^2+3n+2}{n}\\
=\frac{(n+1)(n+2)}{2}
\end{split}
\end{equation}
So, lets prove this:
\begin{equation}
\sum^{n}_{k=0}r^k=\frac{r^{n+1}-1}{r-1}
\end{equation}
What must be proved in the base case?
In this case, we need to prove that it works for $n=0$.
This is done like so:
\begin{equation}
\sum^{0}_{k=0}r^k=r^0=\frac{r^{0+1}-1}{r-1}=\frac{r-1}{r-1}=1
\end{equation}
Next, we state our inductive hypothesis, that is:
\begin{equation}
\sum^{n}_{k=0}r^k=\frac{r^{n+1}-1}{r-1}
\end{equation}
Finally, we solve for $n=n+1$:
\begin{equation}
\begin{split}
\sum^{n+1}_{k=0}r^k=\sum^{n}_{k=0}r^k+r^{n+1}\\
=\frac{r^{n+1}-1}{r-1}+r^{n+1}\\
=\frac{r^{n+1}-1}{r-1}+\frac{(r-1)r^{n+1}}{r-1}\\
=\frac{\cancel{r^{n+1}}-1+r^{n+2}-\cancel{r^{n+1}}}{r-1}\\
=\frac{r^{n+2}-1}{r-1}
\end{split}
\end{equation}
\end{document}